Spatiotemporal dynamics and sustainable pathways of water ecological footprint in northeast Sichuan, China - Pan, An; Cao, Longyu; Shu, Chengqiang; Yang, Ying; Zhou, Heng; Cong, Rui (Frontiers in Environmental Science, 2026)
Given the characteristics of water resources in Northeast Sichuan, a systematic evaluation system for water resources utilization was developed based on the water resources ecological footprint model and calculation methods. This system was applied to analyze the ecological footprint of water resources and the sustainable development capacity of Northeast Sichuan from 2013 to 2022. The results showed the following: (1) The ecological footprint of water resources in Northeast Sichuan increased by a total of 1.35 × 106 ha(hectare) from 2013 to 2022, with the largest per capita ecological footprint of water resources in each city being Guangyuan and the smallest being Bazhong. (2) The ecological carrying capacity of water resources in the region varies greatly from year to year, mainly affected by the total amount of water resources and the amount of precipitation in that year, with large spatial differences between districts and counties, and a general downward trend. (3) The ecological footprint of water quality shows a trend of first increasing and then continuously decreasing, indicating that the treatment rate of wastewater is continuously improving. The value of water resources’ ecological footprint of 10,000 yuan GDP (Gross Domestic Product) in each district and county basically stays around 0.10 ha, and the utilization efficiency of water resources is improving. (4) Water resource utilization and economic growth in Northeast Sichuan are in a weakly decoupled state, and economic growth is still dependent on water resource consumption, and benign development is not stable enough. In the future, attention will be paid to the ecological protection of water resources to avoid possible ecological risks and water scarcity. This will ensure the sustainable development of water resources.